Research Design and Methods : A Process Approach - Bordens, Kenneth S.; Abbott, Bruce B. (New Delhi McGraw-Hill Education, 2011)
Takes students through the research process, from getting and developing a research idea, to designing and conducting a study, through analyzing and reporting data. Information on the research process is presented in a lively and engaging way, highlighting the numerous decisions that must be made when designing and conducting research.
Include Figures, Appendix, Glossary, References and Indexes.
Keywords: Psychology--Research -- Psychology--Research--Methodology -- Psychology--Methodology